Cultural Diversity in the Classroom and its Effects on Academic Performance : a Cross-National Perspective - N'Dri Konan, Paul [Verfasser]; Chatard, Armand [Verfasser]; Selimbegovic, Leila [Verfasser]; Mugny, Gabriel [Verfasser] (My University, 2010)
"Drawing on data from the Organization for Economic Cooperation and Development’s Program for International Student Assessment (OECD/PISA), we examined the relationship between the percentage of immigrant students and the reading and mathematics performances of native and immigrant students across nations. In line with research on cultural diversity, results indicated performance benefits as the percentage of immigrant students increased across nations. Interestingly, these effects remained significant for both native and immigrant students, once several other predictors of test performance at the national, school, and individual levels were controlled for. These findings challenge the assumption that the increasing presence of immigrant students in educational institutions represents a threat to native students' academic performance. Potential mechanisms are proposed and discussed, offering new avenues for research." (Autorenreferat, BIBB-Doku)
Keywords: P 1.5 Migranten; G 2.1.2 Interkulturalität; S 1.1 Allgemeinbildende Schule; Heterogenität; Interkulturalität; Schulleistung